2015
DOI: 10.1016/j.matdes.2015.06.099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short time milling in R5(Si,Ge)4, R = Gd and Tb, magnetocaloric materials

Abstract: The effect of the short milling times on R5(Si,Ge)4 R =Gd, Tb magnetocaloric material properties was investigated. In particular, the effect of milling on atomic structure, particles size and morphology, magnetic, and magnetocaloric effect was studied. With short milling times (< 2.5h), a reduction of the Gd5Si1.3Ge2.7 and Tb5Si2Ge2 particles size was achieved down to approximately 3.5 µm. For both compositions the main differences are a consequence of the milling effect on the coupling of the structural and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 51 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…59 One of the most popular approaches for down-sizing magnetocaloric materials has been ball-milling as Blasquez and coworkers have reviewed, 60 and this technique has been intensively used in particular for the R 5 (Si,Ge) 4 materials. [61][62][63] It was observed that for materials with first-order magnetostructural transitions, the ball-milling and consequent sizereduction (downwards to the 0.5-5 lm range) lead to a strong attenuation of the respective MCE, which is explained by the increasing amorphization with increasing milling time. However, our group unveiled the mechanism that is ruling the different behaviors: it is an induce internal strain arising from the ball-milling process during the formation of microparticles.…”
Section: B R 5 (Sige)mentioning
confidence: 99%
“…59 One of the most popular approaches for down-sizing magnetocaloric materials has been ball-milling as Blasquez and coworkers have reviewed, 60 and this technique has been intensively used in particular for the R 5 (Si,Ge) 4 materials. [61][62][63] It was observed that for materials with first-order magnetostructural transitions, the ball-milling and consequent sizereduction (downwards to the 0.5-5 lm range) lead to a strong attenuation of the respective MCE, which is explained by the increasing amorphization with increasing milling time. However, our group unveiled the mechanism that is ruling the different behaviors: it is an induce internal strain arising from the ball-milling process during the formation of microparticles.…”
Section: B R 5 (Sige)mentioning
confidence: 99%
“…Similarly, the amount of detected eutectic phase was found to increase for Gd 5 Si 4 compound when the particle size reduces from 700 to 80 nm through ball milling 29 . Previously, it was shown an enlargement of secondary R 5 M 4 phases, such behavior was observed for milled Gd 5 Si 1.3 Ge 2.7 and Tb 5 Si 2 Ge 2 followed by a reduction on the unit cell volume of the main phase 11 . In our case, by sieving the GSG powders, a slight increase on the unit cell volume of the main O(I) phase from 865 A 3 for the bulk to 869Å 3 for the 3.4 µm powder was noted, while M and 5:3 unit cells remain unchanged, as summarized on Table I.…”
Section: A Crystallographic and Morphological Characterizationmentioning
confidence: 58%
“…Such observation is confirmed through the appearance of a bump highlighted at the dM/dT curves 25 . It is worth to point out that the reduction of particle size seems to be affecting only the secondary M-phase since there is no shift on T C for the main O(I) phase, as usually observed in magnetic materials at the micro/nanoscale 11,35,36 . Such effect can be rising from the higher sensitivity of the M structure over O(I) to applied magnetic field, hydrostatic pressure and particle size 31,37 .…”
Section: B Magnetic Characterizationmentioning
confidence: 79%
See 2 more Smart Citations